The Legal Protection for Banking Parties through Buy Back Guarantee Agreements to Support Guarantees for Home Purchases with a Home Ownership Credit System - Dayan Panaya; Siti Rodhiyah; Setyawati Setyawati (Sultan Agung Notary Law Review, 2022)
This study aims to (1) determine and analyze the legal standing of the buy back guarantee agreement as a guarantee for the purchase of a house through a home ownership loan. (2) To find out and analyze the legal protection for banks through a buy back guarantee agreement as a supporter of a guarantee for the purchase of a house with a home ownership credit system. This research is descriptive with a sociological juridical approach. The data collected in the form of primary data and secondary data. Data was collected through field studies and literature studies. Data were analyzed with quantitative descriptive. The results of the study show that (1) The Legal Position of the Buy Back Guarantee Agreement is categorized as a guarantee agreement.